(untitled) - Ingraham, John L. (Pacific Grove, CA, United States, 2004)
This book include 5 part: part1: principles of microbiology, part2: The microoganism, part3: principles of human-microbe interaction, part 4: Human disesses caused by microorganisms, part 5: Benefits and uses of microorganisms
Keywords: Microbiology,Medical microbiology